Topical Fluoride application among Pediatric outpatients - A retrospective study - A, TRISHALA; P, JESSY; B, ARTHI (The journal of contemporary issues in business and government, 2021)
Widespread use of fluoride has been a major factor towards the decline in both the prevalence and severity of dental caries in economically developed countries. Fluorides prevent tooth decay by promoting remineralization and inhibiting demineralization of enamel. It is recommended as part of a comprehensive tooth decay prevention program. The growing number of parents who refuse topical fluoride in clinical practice warrants attention from dental professionals and the scientific community. The goal of this research is to know the level of acceptance of fluoride treatment. The aim of this study was to evaluate the acceptance of topical fluoride application among pediatric dental patients. A retrospective study was conducted using the patient records from Saveetha Dental College, Chennai from June 2019 - April 2020. The study population included pediatric patients with dental caries, selected by non-probability purposive sampling. Data was collected and then subjected to statistical analysis. Microsoft Excel 2016 (Microsoft office 10) data spreadsheet was used to collect data and later exported to SPSS IBM (version 20.0). Descriptive statistics and chi square test were employed with a level of significance set at p<0.05. It has been concluded that the overall acceptance of fluoride application was 20.72%, among which 80.34% of the patients preferred fluoride gel and 19.66% preferred fluoride varnish. Children between 6-13 years of age and children with higher dental caries, especially males, had a more favourable level of acceptance.Thus the most parental acceptance was noticed only after progression of decay in children. There is a paramount need to educate the parents and caregivers about the importance of topical fluoride application as a preventive measure in preventing caries and progression of decay in children.